Effects of Profanity on the Kitchen Employees of Jollibee in SM North Edsa Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the effect of profanity on the kitchen employees ofJollibee in Sm. North Edsa, Quezon City, in terms of work stress, work productivity, jobsatisfaction, work environment, and work performance. Profanity at work is a problem in somefood industries, as it can be used to express emotions, vent, and release, but it can also beseen as disrespectful and rude and cause disciplinary action.From the results of this study, The majority of the respondents are females who are workingon food preparation in the morning shift. Most of them are experiencing personal issues withtheir coworkers and a toxic environment inside their workplace that can cause them to not beproductive and not be satisfied with their work because of the profanity that they experience.This study recommends that individuals talk about the problems that can cause unhealthyrelationships at work or confront the person who is involved. Hold a meeting if there are badthings happening in the workplace and discuss the situation of employees if they experiencebad treatment in the workplace. Be professional and be a good example to employees. Don'tlet your temper get to you. Create a policy that prohibits the use of bad language at work. Givethe right to punish anyone who disobeys it. Do activities that will help the employees to have agood relationship with each other.
Keywords: Hospitality Management